Globalization and the politics of development in the Middle East - Henry, Clement M. (The contemporary Middle East., 2010)
"In a new edition of their book on the economic development of the Middle East and North Africa, Clement Henry and Robert Springborg reflect on what has happened to the region's economy since 2001. How have the various countries in the Middle East responded to the challenges of globalization and to the rise of political Islam, and what changes, for better or for worse, have occurred? Utilizing the country categories they applied in the previous book and further elaborating the significance of the structural power of capital and Islamic finance, they demonstrate how over the past decade the monarchies (as exemplified by Jordan, Morocco, and those of the Gulf Cooperation Council) and the conditional democracies (Israel, Turkey, and Lebanon) continue to do better than the military dictatorships or "bullies" (Egypt, Tunisia, and now Iran) and "the bunker states" (Algeria, Iraq, Libya, Sudan, Syria, and Yemen)"--